2020
DOI: 10.1108/gs-12-2019-0062
|View full text |Cite
|
Sign up to set email alerts
|

Application of grey clusters in the development of a Synthetic Model of the goals of Polish family enterprises' successors

Abstract: PurposeThe knowledge of goals of the successor, who is preparing to take over the business, is extremely important for the succession process and further operation of a family enterprise. The aim of this study is to structure the goals of Polish family enterprises’ successors and to develop a Synthetic Model of the goals of Polish family enterprises' successors with the application of grey clustering evaluation models.Design/methodology/approachResearch into the specifics of the diagnosis and assessment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Geographical Indications, as marks of designation for food products, can be used in different ways [40][41][42][43]. The current standards of production of the European Union are not easy to reach, however, this might be viewed as a significant challenge to enhance the overall Albanian agricultural sector [44].…”
Section: Discussionmentioning
confidence: 99%
“…Geographical Indications, as marks of designation for food products, can be used in different ways [40][41][42][43]. The current standards of production of the European Union are not easy to reach, however, this might be viewed as a significant challenge to enhance the overall Albanian agricultural sector [44].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that consumers respond less to digital assistant technology resembling them [17], the use of social media in electronic commerce positively affects purchase intention and brand value [18], and consumer loyalty in social commerce differs according to consumer preferences, interaction, and disclosure of personal information [19]. In SMEs, assessment of goals for the dynamics of advanced businesses [20]; which are of great importance for manufacturers, the criteria of security and privacy, corporate risk, sharing and cooperation have been found to be significant in adopting cloud computing, one of the first steps of digitalization [21].…”
Section: Developing a Digitalization Scalementioning
confidence: 99%
“…In addition to these methods, in the assessment of the goals of successful family businesses in Poland by Janka et. al., application of grey clustering evaluation models [20] were used.…”
Section: Digital Maturity Modelmentioning
confidence: 99%
“…There are many methods to deal with uncertainty [20,21,22].Because the demand for vegetable and fruit agricultural products fluctuates greatly and lacks accurate relevant data, we decided to adopt the method of fuzzy chance-constrained programming, and use the possibility (Pos) measure to deal with the uncertainty of demand in the model, in order to reduce the impact of fuzzy parameters on network optimization, so formula (3) can be converted into: (19) Relevant theorems are introduced below.…”
Section: Fuzzy Theorymentioning
confidence: 99%